Knowledge and Attitude Regarding Infection Control among Undergraduate Dental Students at a Tertiary Care Hospital - Acharya, Pujan; Baral, Ratna; Shrestha, Sajeev; Baral, Dharanidhar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: In academic institutes, dental students are not only involved in academic activities, but also in the management of patient care. This calls for inculcation of adequate knowledge and positive attitude among them so that a good clinical practice is implemented in the dental setting. Objective: To assess knowledge and attitude regarding infection control among undergraduate dental students of B.P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Sunsari, Nepal. Methods: An online analytical cross-sectional study was conducted at BPKIHS from 2021 February to 2021 April among undergraduate students from third year, fourth year, and internship by using a self-administered questionnaire via Google Forms. Census method was used. Descriptive and inferential statistics were used to analyse the data. Results: A total of 136 undergraduate dental students participated out of which 107 (78.70%) were found to have adequate knowledge while 101 (74.30%) participants showed ‘positive’ attitude. Mean age of the participants with adequate knowledge was significantly higher than participants with inadequate knowledge (P=0.047). The difference in knowledge among participants was statistically significant (P=0.001) in academic years. Adequate knowledge was shown by 47 (90.4%) interns followed by 36 (83.7%) fourth year and 24 (58.7%) third year students. The difference in attitude was also statistically significant (P=0.011) across the academic years. Positive attitude was shown by 39 (90.4%) fourth year students followed by 28 (68.3%) third year students and 34 (65.4 %) interns. Conclusions: The present study reports adequate knowledge and positive attitude regarding infection control among undergraduate dental students in BPKIHS.